Analisis Kebutuhan Pengembangan Media AR Berbasis PBL untuk Memfasilitasi Kemampuan Literasi Numerasi Peserta didik - Dewanti, Hafizha Arwa; Rahmawati, Dwi; Anwar, Rahmad Bustanul (Jurnal Pendidikan Matematika Universitas Lampung, 2025)
Numeracy literacy skills are one of the indicators of quality education goals. With the advancement of technology, technology has been utilized in education as a learning media like Augmented Reality (AR). The purpose of this research is to determine the learning media that need to be developed to facilitate students' numeracy literacy skills. This study uses a qualitative descriptive research method with the research subjects are 28 eighth-grade students of SMP Muhammadiyah Ahmad Dahlan. The sampling technique is purposive sampling. The instruments were observation sheets, interview guides, and tests. Data analysis with qualitative analysis for observation and interview data, then descriptive statistics for test data. The results showed that there were still many students who got daily test scores below the school's KKM, the learning media used was still minimal and there were not many contextual problems in the learning content, so it had not facilitated students' numeracy literacy skills. Based on the research, it is concluded that the development of learning media to facilitate students' numeracy literacy skills is impresive. AR-based Problem-Based Learning (PBL) media can be an alternative. The PBL stages presented in AR can support the improvement of students' numeracy literacy skills.